Guided biofilm therapy before recession type 2 coverage: Case report - Leonardo Jaya Setiadi Tanumiharja; Winny Suwindere; Edria Benita Tampubolon; Tasya Virania Adristi; Michella Wynne Wijaya (International Journal on Health and Medical Sciences, 2026)
Recession Type 2 defects are challenging because interproximal attachment loss reduces the predictability of complete root coverage. This case report describes the integration of a structured Guided Biofilm Therapy protocol into presurgical and supportive care for a 26-year-old male smoker with a Recession Type 2 defect at tooth 41 after unsuccessful orthodontic treatment. At baseline, the plaque index was 93% and bleeding on probing was 36%. Tobacco-cessation counselling, individualised oral-hygiene instruction, biofilm disclosure, air polishing, and site-specific instrumentation were provided over three preparatory visits. Before surgery, the plaque index and bleeding on probing had decreased to 7% and 4%, respectively. The defect was then treated with a laterally closed tunnel and a palatal subepithelial connective tissue graft. At 6 months, the plaque index was 11% and bleeding on probing was 5%; at 12 months, the corresponding values were 7% and 5%. Complete clinical root coverage was maintained at both follow-ups, and serial radiographs showed changes suggestive of increased interproximal bone fill. The favourable outcome followed a combined program of risk-factor control, professional biofilm management, surgery, and maintenance; the independent effect of Guided Biofilm Therapy cannot be determined from a single case. Standardised controlled studies are required to clarify its adjunctive value in periodontal plastic surgery.